Prevalence of Congenital Heart Defects among Neonates in Port Harcourt, Rivers State, Nigeria - O Amaewhule; BE Otaigbe; PI Opara (Journal of Hypertension and Cardiology, 2022)
Introduction Congenital Heart Defects (CHDs) are structural abnormalities of the heart and intra-thoracic great vessels that are present at birth and may be of functional significance. They are the most frequently occurring congenital anomalies and babies born with severe forms of these defects are likely to die in the neonatal period. Objectives The aim of this study was to determine the prevalence of CHDs among neonates delivered in Port Harcourt, Rivers State, Nigeria Methods Using a stratified sampling technique, 530 neonates were selected from three hospitals in Port Harcourt. The biodata of the parents and socio-demographic information were obtained through an interviewer-administered questionnaire to the mothers. Physical examination and echocardiograghy were performed on all the neonates. Results Five hundred and thirty (530) neonates aged 0-7days (5.2±1.8) participated in this study and the male to female ratio was 1.1:1. Forty-three neonates were found to have CHD giving a prevalence of 8.1% 95%CI: 6.0. Thirty-nine were acyanotic and four cyanotic. Congenital Heart Defects were found in 21 (48.8%) males and 22 (51.2%) females. The more common heart defects were isolated Atrial Septal Defect in 16(37.2%), isolated Patent Ductus Arteriosus in 11(25.6%) and isolated Ventricular Septal Defect in 6 (13.9%). The most common cyanotic CHD was Transposition of the Great Arteries in 2 neonates (4.7%). The clinical features identified in neonates with CHD were tachypnoea, dysmorphia, cyanosis, hypoxia and murmur Conclusion The prevalence of CHD is considerably high in Port Harcourt and further studies need to be carried out to ascertain the risk factors.
Keywords: Tachypnoea